Dependable and historic computing essays dedicated to Brian Randell on the occasion of his 75th birthday - Jones, Cliff B.; Lloyd, John L. (Lecture notes in computer science, 2011)
This Festschrift volume, published in honor of Brian Randell on the occasion of his 75th birthday, contains a total of 37 refereed contributions. Two biographical papers are followed by the six invited papers that were presented at the conference 'Dependable and Historic Computing: The Randell Tales', held during April 7-8, 2011 at Newcastle University, UK. The remaining contributions are authored by former scientific colleagues of Brian Randell. The papers focus on the core of Brian Randell?s work: the development of computing science and the study of its history. Moreover, his wider interests are reflected and so the collection comprises papers on software engineering, storage fragmentation, computer architecture, programming languages and dependability. There is even a paper that echoes Randell?s love of maps. After an early career with English Electric and then with IBM in New York and California, Brian Randell joined Newcastle University. His main research has been on dependable computing in all its forms, especially reliability, safety and security aspects, and he has led several major European collaborative projects.